Determination of Custody Rights (Hadhanah) for Children Who Are Not Yet Mumayiz to the Father - Rohmah, Asantia Puspita; Suyaman, Prahasti; Mulyanti, Asti Sri (Rechtsnormen: Journal of Law, 2023)
Background. One of the legal consequences of the breakdown of marriage due to divorce is the custody of children, which in fiqh literature is called Hadhanah. Purpose. The purpose of this paper is to: (a) provide information on the distribution of hadhanah rights to fathers for children who are not yet Mumayiz due to divorce. Method. The research method used in this research is a qualitative method with the type of normative juridical research based on primary and secondary legal materials, namely research that refers to the norms contained in the legislation. Hadhanah is a right that must be fulfilled by adults who are required to take care of the needs of a child including providing education and support to children who are not old enough. Results. The results of this study indicate that hadhanah in Islamic law prioritizes the best interests of the child. This is in accordance with the basic principles of Islamic law (found in the Qur'an and Hadith), which state that children have inherent rights in relation to both parents. Likewise, it is used in positive law in Indonesia. Parental authority over children after divorce according to the provisions of the two laws (Islamic Law and Indonesian Positive Law) is in line. Both divorced parents must continue to fulfill their children's hadhanah in accordance with the rights of children in the Child Protection Law, namely, the rights to life, growth, protection and participation. Conclusion. Therefore, when a divorce occurs, it will have certain legal consequences, especially the issue of Hadhanah (child custody). Hadhanah itself in fiqh terms is used two words but intended for the same purpose, namely Kafalah and Hadhanah. what is meant by Hadhanah or Kafalah in a simple sense is 'Maintenance or 'Care.